The role of MALL-based dubbing in developing oral English skills: a pilot study - Qiuyao, Wang; Zhao, Sun; Noordin, Nooreen (Human Resource Management Academic Research Society, 2024)
This pilot study explores the impact of MALL-based dubbing on students’ oral English proficiency, as well as their preferences and attitudes towards this learning approach. The participants were 10 sophomore students from a university in southern China. Data collection included pre-test and post-test analytic scores focusing on complexity, accuracy, and fluency (CAF) through objective ratings, alongside descriptive data from two questionnaires. The findings revealed that engaging in MALL-based dubbing improved students’ oral English proficiency, particularly in terms of speech rate. Additionally, learners expressed preferences for dubbing tasks with characteristics such as durations of 30 seconds to 2 minutes, three tasks per week, and a standard pace. Most participants demonstrated a positive attitude toward this approach.